Cesarean Scar Pregnancies: Experience of 60 Cases. (1st April 2015) - Timor-Tritsch, Ilan E.; Khatib, Nizar; Monteagudo, Ana; Ramos, Joanne; Berg, Robert; Kovács, Sándor
Abstract : Objectives: To evaluate the management, clinical courses, and outcomes of cesarean scar pregnancies diagnosed in the first trimester. Methods: We identified 60 cases of cesarean scar pregnancies diagnosed between 5 and 14 weeks. Group A contained 48 patients with fetal/embryonic cardiac activity; group B comprised 12 patients without cardiac activity; and group C included 11 patients with cardiac activity who chose expectant management. Results: Five of the 48 patients (10.4%) in group A were successfully treated for vaginal bleeding. Thirty‐three (68.7%) received methotrexate injections, and all had full resolution. Three (6.3%) required uterine artery embolization for late‐developing arteriovenous malformations. Ten of the 12 patients (83.3%) in group B were managed expectantly and had full recovery. Two of the 10 (20.0%) had arteriovenous malformations; 1 had unsuccessful uterine artery embolization followed by a hysterectomy, and the second requested a hysterectomy. Ten of the 11 patients (90.9%) in group C continued the pregnancies. One declined local injection. Four of the 10 (40.0%) delivered live offspring by successive elective cesarean deliveries. Three (30.0%) had hysterectomies for placenta percreta, and 1 did not have a hysterectomy after delivery. Five (50%) had second‐trimester complications, all leading to hysterectomies. Of the 60 patients, 20 (33.3%) had serious complications: 5 had arteriovenous malformations; 4 had uterine artery embolization; and 11 had hysterectomies. Conclusions: A cesarean scar pregnancy is a serious complication for patients who have had cesarean deliveries. Counseling, treatment, and follow‐up are challenging for patients and caregivers. However, emerging data from different management approaches confirm that a cesarean scar pregnancy may progress and result in a live neonate at the expense of further fertility. This study confirmed that expectant management of a cesarean scar pregnancy is associated with a high risk of hysterectomy due to morbidly adherent placenta.